CMA 102 - Medical Terminology & Body Systems 2 - Linn Benton Virtual College (2018)
Medical Terminology and Body Systems II prepares you to list major organs in each body system, describe their function, and identify and analyze pathologies related to each system. You will be able to discuss implications for disease and disability as it relates to each system, as well as issues related to treatment for each pathology and how it changes throughout the lifespan. This course has 4 Credit Units that will assist you in learning the course objectives.